Look Again - Scottoline, Lisa.; Masterson, Mary Stuart, 1966- (New York : Macmillan Audio, 2009)
When reporter Ellen Gleeson gets a "Have You Seen This Child?" flyer in the mail, the child looks exactly like her adopted son, Will, which prompts Ellen to launch an investigation that ultimately threatens both of their lives.
Unabridged.
Compact discs.
Read by Mary Stuart Masterson.
Keywords: Women journalists -- Fiction; Missing children -- Fiction; Adopted children -- Fiction; Audiobooks; Suspense fiction